2006
DOI: 10.1038/nsmb1060
|View full text |Cite
|
Sign up to set email alerts
|

The hybrid state of tRNA binding is an authentic translation elongation intermediate

Abstract: The GTPase elongation factor (EF)-G is responsible for promoting the translocation of the messenger RNA-transfer RNA complex on the ribosome, thus opening up the A site for the next aminoacyltRNA. Chemical modification and cryo-EM studies have indicated that tRNAs can bind the ribosome in an alternative 'hybrid' state after peptidyl transfer and before translocation, though the relevance of this state during translation elongation has been a subject of debate. Here, using pre-steady-state kinetic approaches an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
140
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(162 citation statements)
references
References 42 publications
22
140
0
Order By: Relevance
“…12) and is the rate-determining step for the process. Steps 4 and 5 may be conformationally linked: thus, EF-G-dependent translocation is accelerated by either mutation of the 50S A site or lengthening of the peptidyl group (17), and each of these changes promotes the A/A-to-A/P transition (4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12) and is the rate-determining step for the process. Steps 4 and 5 may be conformationally linked: thus, EF-G-dependent translocation is accelerated by either mutation of the 50S A site or lengthening of the peptidyl group (17), and each of these changes promotes the A/A-to-A/P transition (4).…”
Section: Discussionmentioning
confidence: 99%
“…Effects of antibiotics and ribosomal mutations indicated that, although both events are limited by the unlocking step, codon-anticodon movement and P i release are independent of each other and probably occur in random order (12)(13)(14). Finally, ribosomal rearrangements must occur to ''relock'' the tRNAs in their new sites, followed by release of EF-G⅐GDP from the POST complex, although the kinetics of these events have yet to be fully characterized.A number of studies suggest an important role for hybrid-state formation in the mechanism of EF-G-dependent translocation (11,(15)(16)(17). However, it remains unclear how the P/P-to-P/E and A/A-to-A/P transitions relate to the kinetically defined events of translocation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1; Samaha et al 1995;Kim and Green 1999). While the specific interactions of tRNAs in classical positions are critical for both peptide bond formation (Lieberman and Dahlberg 1994;Weinger et al 2004;Brunelle et al 2006;Dorner et al 2006) as well as peptide release (Feinberg and Joseph 2006), such contacts must be extensively remodeled for tRNA substrates to move directionally through the ribosome during active translation (Agirrezabala and Frank 2009;Munro et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Translocation can be broadly divided into two steps. First, the tRNAs move on the large subunit from their classical A/A and P/P states to their hybrid A/P and P/E states (1,2), facilitated by intersubunit rotation, which can occur spontaneously and reversibly (3)(4)(5)(6)(7). During the second step, which is rate limiting and EF-G-dependent (8,9), the tRNA anticodon stem-loops (ASLs) and their associated mRNAs move from the A to P and P to E sites of the small subunit, thereby advancing the tRNAs into their classical P/P and E/E states.…”
mentioning
confidence: 99%